Wireless monitoring for combined-cycle solar energy self-sustaining membrane distillation (MD) and membrane distillation bioreactor (MDBR) water production and recycling system - Oon, You Yi. (2009)
Global warming and climate changes had always been an impacting issue. It had caught the attention of the world to response and act upon solving it. More engineers and researchers around the globe were aware of the issues and already putting these thoughts into consideration when creating new product for their market. As for Nanyang Technological University, these issues were not forgotten and had always being put into consideration. To elevate the awareness of the need for being environmental friendly, a number professors Electrical and Electronic Engineering had participated the Competitive Research Program (CRP) in the search for new green solutions. One of the CRP project the professors came out with was the designing of “zeroenergy” green water production and recycling system using Membrane Distillation (MD) and Membrane Distillation Bioreactor (MDBR). The student was then involved in this CRP project as part of his Final Year Project which will be included in this final year report. This report covers the research and prototyping of wireless monitoring solutions incorporating into the whole prototype system. In this research, the student had come out with few methods for different types of communication needs. Methods that consist of internet, Global Service for Mobile communication (GSM) and Wireless Personal Area Network (WPAN) communication were put into the main considerations. He had also done research on the three methods and proceeded with WPAN as part of his first implementation. The primary focus of monitoring the system is by temperature, humidity and light. The student had started off and worked on the first prototype, which was running on one of the WPAN communication methodology by using ZigBee made by JENNIC. ZigBee is a specification for small-in-size and low-powered wireless device for IEEE 802.15.4-2006 standards for the Wireless Personal Area Network (WPANs). The complete ZigBee kit the student had purchased from was Jennic.